Nile basin land and water acquisition research agenda: A policy brief - Enserink, Bert; Abazeed, Abeer; Elhatow, Lama; Muricho Onencan, Abby (International Journal of Water Governance, 2022)
Land and water acquisitions exacerbate the complexity of the water allocation challenges in the Nile region and consequently have contributed to the growing tensions along the Nile River. Smallholders are especially negatively affected by the increase in water use by foreign investors, the loss of access to the commons, and disposition of ownership. This policy brief is a result of a scenario workshop organized in early 2020 in Leiden, the Netherlands, during which some 30 young scientists from a variety of disciplines joined forces to develop four plausible Nile-futures in 2050. The exercise revealed new challenges and potential knowledge gaps in four areas of policy-based research: local innovation and technology, institutional capacity, gover- nance, and investment regulation. Most urgent was the recommendation to have a unified basin- wide university, which would support basin-wide legislation to promote sustainable farming and reduce the negative impacts of land and water acquisitions.